Quantification of Atazanavir and Ritonavir in Human Plasma Samples by Rp- Hplc Include Method of Detection in the Title, Eg: Using Pda Detection: Pharmaceutical Science-Pharmaceutical analysis for Novel drug formulation - Abhinandana.Patchala; Ramarao Nadendla (International Journal of Life Science and Pharma Research, 2022)
A fixed oral dose combination of Atazanavir and Ritonavir is currently used for the treatment of patients with HIV infections. A selective and novel bio-analytical technique was designed to evaluate Atazanavir and Ritonavir by mass spectroscopic investigation in plasma matrices. The method was chromatographed with Agilent TC-C18, 4.6 x 75 mm, 3.5 µm, 80 Å column, 5mM ammonium acetate: acetonitrile (20:80 v/v) mobile phase was used for Chromatographic separation. UV detector was used to detect the Atazanavir and Ritonavir at 235 nm. For extraction of the analyte and internal standard, Liquid-liquid extraction was employed .This method is validated over a linear concentration range of 50.0 – 10000.0 ng/ml for Atazanavir and Ritonavir with a correlation coefficient (r) of = 0.9997 and both drugs were stable in plasma samples.